(2m^2 + 3m + 1) (m^2 - 3m -2)

Step 1: Multiply each term of the first bracket by the terms in the second bracket

(2m2 +3m + 1) (m2 -3m -2)

= 2m2(m2- 3m -2) +3m(m2- 3m -2) + 1(m2- 3m -2)

= 2m4 - 6m3 -4m2 + 3m3 - 3m2 - 6m + m2 -3m -2

Step 2 : collect the like terms and combine them

= 2m4 -6m3 + 3m3- 4m2 -3m2 + m2 - 6m- 3m -2

= 2m4 + 3m3 - 6m2 - 9m -2

The solution is 2m^4 - 3m^3 - 6m2 - 9m - 2.

I am counting checking, if there will be any corrections I will communicate in the next 5 minutes.

There is a correction

2m2(m2-3m-2) = 4m4 - 6m3 -4m2

3m(m2-3m -2) = 3m3- 9m2 - 6m ....... // correction made

1(m2 -3m -2) = m2 -3m -2

Combining them

= 4m4 - 6m3 - 4m2 +3m3 - 9m2- 6m + m2- 3m- 2

= 4m4- 6m3 + 3m3 - 4m2 - 9m2 +m2 - 6m - 3m- 2

= 4m4 + 3m3 -12m2 - 9m - 2

= 4m^4 + 3m^3 -12m^2 - 9m -2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up